Strategic Approach to Participatory Forest Management in Himachal Pradesh–The Way Forward - Vasudeva, S.P. (Indian Forester, 2019)
The concept of Joint Forest Management (JFM) is based on interaction and relationship between village communities and Forest Department wherein benefits from forests managed under this concept is shared by both, the ratio of which varies from State to State. JFM lacks legal sanctity, clarity on benefit sharing arrangements and has not given results that were expected after three decades of its implementation. The strategic Participatory Forest Management (PFM) Approach model developed for Himachal Pradesh (HP) covers lacunae observed in JFM implementation and can be considered for implementation in HP and in the country. Such an approach would lead to improved productivity of all categories of forests treated separately. It would also lead to environmental conservation, livelihood generation and improvement in socio-economic status of people.